Transcriptional landscape of pathogen‐responsive lncRNAs in rice unveils the role of ALEX1 in jasmonate pathway and disease resistance - Yu, Yang; Zhou, Yan‐Fei; Feng, Yan‐Zhao; He, Huang; Lian, Jian‐Ping; Yang, Yu‐Wei; Lei, Meng‐Qi; Zhang, Yu‐Chan; Chen, Yue‐Qin (Plant biotechnology journal, 2020)
Summary Plant defence is multilayered and is essential for surviving in a changing environment. The discovery of long noncoding RNAs (lncRNAs) has dramatically extended our understanding of post‐transcriptional gene regulation in diverse biological processes. However, the expression profile and function of lncRNAs in disease resistance are still largely unknown, especially in monocots. Here, we performed strand‐specific RNA sequencing of rice leaves infected by Xanthomonas oryzae pv. Oryzae (Xoo) in different time courses and systematically identified 567 disease‐responsive rice lncRNAs. Target analyses of these lncRNAs showed that jasmonate (JA) pathway was significantly enriched. To reveal the interaction between lncRNAs and JA‐related genes, we studied the coexpression of them and found 39 JA‐related protein‐coding genes to be interplayed with 73 lncRNAs, highlighting the potential modulation of lncRNAs in JA pathway. We subsequently identified an lncRNA, ALEX1, whose expression is highly induced by Xoo infection. A T‐DNA insertion line constructed using enhancer trap system showed a higher expression of ALEX1 and exerted a significant resistance to rice bacterial blight. Functional study revealed that JA signalling is activated and the endogenous content of JA and JA‐Ile is increased. Overexpressing ALEX1 in rice further confirmed the activation of JA pathway and resistance to bacterial blight. Our findings reveal the expression of pathogen‐responsive lncRNAs in rice and provide novel insights into the connection between lncRNAs and JA pathway in the regulation of plant disease resistance.